2011
DOI: 10.1007/s10886-011-9942-3
|View full text |Cite
|
Sign up to set email alerts
|

Density-Related Volatile Emissions and Responses in the Red Flour Beetle, Tribolium castaneum

Abstract: Intraspecific attraction depends both on the cues provided by the attracting individual and the response of the attracted individual. These attracting cues are related not only to current conditions, but also are a reflection of individual and population life history. These relationships were examined by placing red flour beetle, Tribolium castaneum (Herbst.), adults in flasks at increasing densities and monitoring the changes in volatile chemical emission over time. Only certain chemicals were quantified: met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 21 publications
1
25
0
1
Order By: Relevance
“…Quinones are secreted from abdominal and thoracic glands (Markarian et al 1978) and are thought to accumulate in flour in a density-dependent manner (Sokoloff 1977). The individual response to major quinone components also increases as a function of population density (Duehl et al 2011). For instance, exposing a pair of focal beetles to olfactory cues from crowded beetles (presumably, largely quinones) for 3 days decreased female oviposition rate by up to 25% (Sonleitner and Gutherie 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Quinones are secreted from abdominal and thoracic glands (Markarian et al 1978) and are thought to accumulate in flour in a density-dependent manner (Sokoloff 1977). The individual response to major quinone components also increases as a function of population density (Duehl et al 2011). For instance, exposing a pair of focal beetles to olfactory cues from crowded beetles (presumably, largely quinones) for 3 days decreased female oviposition rate by up to 25% (Sonleitner and Gutherie 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Flour conditioning can inßuence beetle behavior. For example, ßour can be more attractive to T. castaneum beetles when Þrst colonized (Hughes 1982), but highly conditioned ßour can become repellent (Duehl et al 2011). Sonleitner (1961 showed that egg cannibalism in adult T. castaneum increased in conditioned ßour compared with fresh ßour.…”
mentioning
confidence: 99%
“…16.1.3). As populations increase, however, the food becomes less nutritious and accumulates toxic concentrations of waste products and benzoquinones (Duehl 2011). Such conditions induce adult dispersal via flight (Zyromska-Rudzka 1966a, b;Sokoloff 1974;Ziegler 1978).…”
Section: Habitat Food Life History and Population Cyclesmentioning
confidence: 99%